2017
DOI: 10.12693/aphyspola.131.1512
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Stability, TGA, and Molecular Docking Investigations of p-Coumaric Acid with Special Relevance to Anti-Cancer and Antibacterial Activity

Abstract: In this work an attempt is made to analysis of the possible different conformers of p-coumaric acid (PCA) by using density functional method. The total energy of four possible conformers were calculated by using B3LYP/6-311G(d,p) method. Computational result identifies that the most stable conformer of PCA is C2. The formation of inter-and intra-molecular hydrogen bonding between -OH and -COOH group gave the evidence for dimer formation for PCA molecule. The highest occupied-lowest unoccupied molecular orbital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 31 publications
(25 reference statements)
0
10
1
Order By: Relevance
“…On the other hand, the results of the present study disagree with the findings of Sathish et al, they reported that p-coumaric acid showed high effect against Staphylococcus aureus and Escherichia coli and moderate effect on Streptococcus pyogenes and Klebsiella pneumonia while it had no effect on Salmonella typhi [44]. The observed different response of the same bacterial species to p-coumaric acid may be attributed to the difference in strains.…”
Section: Resultscontrasting
confidence: 99%
“…On the other hand, the results of the present study disagree with the findings of Sathish et al, they reported that p-coumaric acid showed high effect against Staphylococcus aureus and Escherichia coli and moderate effect on Streptococcus pyogenes and Klebsiella pneumonia while it had no effect on Salmonella typhi [44]. The observed different response of the same bacterial species to p-coumaric acid may be attributed to the difference in strains.…”
Section: Resultscontrasting
confidence: 99%
“…Chlorogenic acid as a major component of Morus nigra was reported to inhibit prostate carcinoma PC3 47 . Similarly, ρ -coumaric acid showed a good cytotoxic activity against gastric cancer 48 and lung cancer 49 . Moreover, protocatechuic acid and chlorogenic acid demonstrated a promising cytotoxic activity against both colon and liver cancer 50 .…”
Section: Resultsmentioning
confidence: 96%
“…The earlier degradation of the PCA-Q-NFC1.0 film was mainly attributed to the dehydroxylation and decarboxylation of the PCA moieties. 47 A higher thermal residue (19.6% vs 15.4%) was achieved for the PCA-Q-NFC1.0 film presumably due to the formation of acidpromoted residues. 48 From their DTG curves in Figure 4b, Q-NFC1.0 exhibited dual peaks, while the triple ones were visible for PCA-Q-NFC1.0.…”
Section: ■ Results and Discussionmentioning
confidence: 91%
“…It can be seen that the onset degradation temperature ( T onset ) of the PCA-Q-NFC1.0 film was 203 °C, lower than that of the Q-NFC1.0 one (247 °C). The earlier degradation of the PCA-Q-NFC1.0 film was mainly attributed to the dehydroxylation and decarboxylation of the PCA moieties . A higher thermal residue (19.6% vs 15.4%) was achieved for the PCA-Q-NFC1.0 film presumably due to the formation of acid-promoted residues .…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation